Students’ Perception of Full Day School System in One of Senior High School - Ulfah Nurhasanah; Muhamad Taufik Hidayat; Amir Hamzah (Institut Pendidikan Indonesia Garut, 2019)
To support education in Indonesia to be more effective, additional time is needed for student‟s learning in school. Therefore, the policy makers created a full day school system where students study longer in school to get more effective learning and education. How do students perceive this full day school system? The aim of this study was to find out the students‟ perception of the full day school system. To achieve that aim, the qualitative method in the form of the case study was chosen, participated by 8 students in one of a Senior High School in Garut. This study was conducted online. It has been done since the pandemic COVID-19 in Indonesia occurred. With this situation, all school activities were closed. The instrument of this study was semi-structured interview by using recording of mobile phone and WhatssApp aplication. The initial questions are used is five questions. The data analysis was used were: Organize and prepare the data for analyses, read through all the data, begin detailed analysis with a coding process, interrelated themes and drawing conclusion. The results of this study showed that: 1) the students felt bored and tired with this system because too many tasks to do at home and they were too long in school; 2) the students agree with this system, because this system is very helpful in their learning process, besides this system can help the students‟ parents in supervising their children. But they really hope that teachers reduce the tasks that have to be carried and have to be done at home. It was then suggested that the teachers did not add the assignments to do at home and work professionally.